From sustainable to resilient cities global concerns and urban efforts - Holt, William G. (Research in urban sociology, 2014)
The United Nations Brundtland Report defines sustainable development as one 'that meets the needs of the present without compromising the ability of future generations to meet their own needs." Embedded in this concept of sustainable development are the needs of the world's poor as well as the limits of environmental technology and social organizations to meet these needs. Urban centers, home to the majority of world's population, are hubs of sustainability innovations. However there are major differences among how these sustainability issues are addressed in the Global North and South. Increasingly, urban areas are moving from sustainability to resilience in dealing with environmental issues. This edited volume addresses sustainability efforts in cities and metropolitan regions around the world. The edition explores sustainable development across four key areas: environment, economic, socio-political, and cultural sustainability. These concepts are examined as they apply to both Global North and South urban areas. This volume includes chapters about applications to urban regions across the globe focusing on the movement from sustainable development to resilient urban centers.